Catheter Foam Sclerotherapy of the Great Saphenous Vein, with Perisaphenous Tumescence Infiltration and Saphenous Irrigation. (November 2017) - Cavezzi, Attilio; Mosti, Giovanni; Campana, Fausto; Tessari, Lorenzo; Bastiani, Luca; Urso, Simone U.
Abstract : Objectives: This was a prospective observational study to assess the short- to mid-term efficacy and safety of catheter foam sclerotherapy (CFS) of the great saphenous vein (GSV), including peri-saphenous tumescence infiltration (PST) and intra-saphenous saline irrigation (ISI), in combination with phlebectomy of the varicose tributaries. Methods: Eighty-eight limbs in 82 patients (19 male, 63 female, mean age 55.7 years) affected by varices related to GSV incompetence were submitted to CFS of the refluxing GSV segment after PST and ISI, combined with phlebectomy of the varicose tributaries. Sodium tetradecylsulfate (STS) 3% + CO2 /O2 sclerosant foam (SF) (median 7 mL) was injected in the GSV trunk (median caliber 7.1 mm) by means of a 4F catheter. Clinical and colour duplex ultrasound (CDU) investigation was performed pre-operatively, and 40 days, 6, 12, and 36 months post-operatively. A visual analogue scale (VAS) was used to assess procedure related symptoms and venous symptoms before and 40 days after the treatment. Results: Clinical recurrence (visible varices) at 40 days, 6 and 12 months was 0%, whereas at 36 months it was 4.7%; VAS pre-operative score of heaviness, pain, and cramps/paraesthesiae decreased from 6 (IQR 6–8) to 1 (IQR 0–3), from 3 (IQR 0–7) to 0 (IQR 0–1), and from 3 (IQR 0–7) to 0 (IQR 0–1) respectively at 40 days. The CDU based occlusion rate at 40 days, 6, 12, and 36 months was 100% (88/88), 100% (88/88), 94.3% (83/88), and 89.4% (76/85) respectively. Six of the nine patent saphenous veins (average diameter 1.4 mm) had anterograde flow (overall 96.5% reflux free GSVs). One superficial venous thrombosis was recorded without any further relevant complication. Conclusions: GSV treatment by means of CFS and adjuvant PST + ISI, combined with phlebectomy of varicose tributaries, proved to be safe and effective in terms of clinical and duplex based outcomes at short/mid-term follow-up.